The Strategy of Paratransgenesis for the Control of Malaria Transmission - Fofana, Aminata; Yerbanga, Rakiswendé Serge; Bilgo, Etienne; Ouedraogo, Georges Anicet; Gendrin, Mathilde; Ouedraogo, Jean-Bosco (Frontiers in Tropical Diseases, 2022)
Insect-borne diseases are responsible for important burdens on health worldwide particularly in Africa. Malaria alone causes close to half a million deaths every year, mostly in developing, tropical and subtropical countries, with 94% of the global deaths in 2019 occurring in the WHO African region. With several decades, vector control measures have been fundamental to fight against malaria. Considering the spread of resistance to insecticides in mosquitoes and to drugs in parasites, the need for novel strategies to inhibit the transmission of the disease is pressing. In recent years, several studies have focused on the interaction of malaria parasites, bacteria and their insect vectors. Their findings suggested that the microbiota of mosquitoes could be used to block Plasmodium transmission. A strategy, termed paratransgenesis, aims to interfere with the development of malaria parasites within their vectors through genetically-modified microbes, which produce antimalarial effectors inside the insect host. Here we review the progress of the paratransgenesis approach. We provide a historical perspective and then focus on the choice of microbial strains and on genetic engineering strategies. We finally describe the different steps from laboratory design to field implementation to fight against malaria.